PEMANFAATAN TANAMAN OBAT SEBAGAI SEDIAAN HERBAL INSTAN - Nafisah Isnawati; Dina Trianggaluh; Kustin; Fitria Meliana Putri; Helmalia Shintawati; Nur Azizah Perdani Puteri Syahuri Syahuri (Jurnal SADEWA, 2023)
This activity aims to introduce the benefits of plants as medicine and improve skills in making instant herbs in Sumber Dandang Hamlet, Kebon Sari District. The method used in this activity is in the form of counseling which contains useful information about and how to make products and packaging of herbal plants from turmeric and tamarind. From this activity it can be concluded that: 1) Plants can be used as medicine 2) This service activity can increase motivation for the community, especially housewives to plant more herbal plants 3) The community improves skills or skills in making instant sour turmeric.